Plantago tunetana (Plantaginaceae) in Tunisia: notes on its morphology, distribution, and ecology - Belhaj Ltaeif, Hela; Sakhraoui, Anis; Hassemer, Gustavo; Castillo, Jesús M.; Elimem, Mohamed; Rouz, Slim (Phytotaxa, 2023)
A review of the available knowledge for the Tunisian-Algerian endemic Plantago tunetana is proposed in the present work. This narrowly endemic species was hitherto known from Tunisia within a very restricted area. Field surveys of its occurrence during the last few years, within its locus classicus, allow to find only one population in Gouraïa locality in north-western Tunisia. IUCN Red List assessment shows that the species could be considered as Critically Endangered and requires the implementation of immediate appropriate measurements to ensure its conservation. Besides, an identification key to subgenera, sections, series and species of the genus Plantago in Tunisia is provided.